If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+15=-3(x-3)
We move all terms to the left:
3x+15-(-3(x-3))=0
We calculate terms in parentheses: -(-3(x-3)), so:We get rid of parentheses
-3(x-3)
We multiply parentheses
-3x+9
Back to the equation:
-(-3x+9)
3x+3x-9+15=0
We add all the numbers together, and all the variables
6x+6=0
We move all terms containing x to the left, all other terms to the right
6x=-6
x=-6/6
x=-1
| 142=1/3(3.14)(r^2)(8.5) | | 61.6=7(m+2.4) | | 5(e+7)=4(e+7) | | 11x-4=-42 | | 95.4=9(m+2.8) | | 3(m+4)-2(2m+3)=-4 | | 13s-8=10s+18 | | 99.9=9(m+2.7) | | x-x-2/3=x-x-3/4 | | 3(w+3)-(w-2)=41 | | 3x-16=2x-1 | | x/5+2x/4-3x/6=18 | | 1x+27=6x-174 | | 3(n+4)=3n+2 | | 3x-(2-x)-5=9 | | -6h+7h=27 | | 4x-32=7x-161 | | 5x-35=4x+12 | | 3(4r+9)=-29 | | 2525=25(p+15) | | 25-c=5 | | 9x+54=7x+154 | | 2525=25(p+25) | | 6x-2-4=24 | | 6x=5x+35 | | 5k+18=-22 | | 9x+126=8x+128 | | 30=-7a+6a | | -4n+11=31 | | 5k-7=-12 | | 5x+15=6x-48 | | 1x-13=7x-133 |